La documentación en el contrato de transporte aéreo de personas y de mercancías - Marco Arcalá, Luis Alberto (2021)
The need of documentation is evident in all different aspects and activities inside of air carriage of passengers and goods, including, of course, the contracts for the provision of this kind of services. However, it is also true that the most relevant documentary instruments in these contracts not only have their own peculiar features, but are also immersed in a process of evolution marked by various phenomena. In this article, the author analyzes the main documentary in the contracts of air carriage of passengers and goods, with special focus on its legal character, functions, composition, way of working, among others. In the same way, he addresses the phenomenon of documental digitization and the effects the COVID-19 pandemic on the different aspects of air carriage. Lastly, he formulates a critical assessment in concerning with the future prospects of this field.